2011
DOI: 10.1007/s10646-011-0716-z
|View full text |Cite
|
Sign up to set email alerts
|

Metal accumulation and evaluation of effects in a freshwater turtle

Abstract: A variety of contaminants have been detected in aquatic and terrestrial environments around the Paducah Gaseous Diffusion Plant (PGDP), Kentucky. The presence of these contaminants at the PGDP may pose a risk to biota, yet little is known about the bioaccumulation of contaminants and associated effects in wildlife, especially in aquatic turtles. The current study was initiated to evaluate: (1) the accumulation of heavy metals (Cd, Cr, Cu, Pb, and Hg) in aquatic ecosystems associated with the PGDP using red-ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 56 publications
7
18
2
4
Order By: Relevance
“…Our results support the use of tissue metal concentrations in turtles as toxicological sentinels in aquatic environments, a technique that has been suggested by numerous researchers but has rarely been implemented in monitoring programs (Tryfonas et al 2006;Yu et al 2011). Further, our finding that some metals appear to accumulate in external tissues (i.e., claw and shell), with concentrations that correlate with internal tissues, suggests that non-lethal sampling could be used to monitor heavy metals in the environment.…”
Section: Metal Accumulation In Tissuessupporting
confidence: 83%
See 2 more Smart Citations
“…Our results support the use of tissue metal concentrations in turtles as toxicological sentinels in aquatic environments, a technique that has been suggested by numerous researchers but has rarely been implemented in monitoring programs (Tryfonas et al 2006;Yu et al 2011). Further, our finding that some metals appear to accumulate in external tissues (i.e., claw and shell), with concentrations that correlate with internal tissues, suggests that non-lethal sampling could be used to monitor heavy metals in the environment.…”
Section: Metal Accumulation In Tissuessupporting
confidence: 83%
“…Painted and snapping turtles in our study wetlands contained measurable concentrations of all metals analyzed (cadmium, chromium, copper, iron, lead, magnesium, manganese, and zinc), some of which may cause physiological stress (Yu et al 2011). Our results support the use of tissue metal concentrations in turtles as toxicological sentinels in aquatic environments, a technique that has been suggested by numerous researchers but has rarely been implemented in monitoring programs (Tryfonas et al 2006;Yu et al 2011).…”
Section: Metal Accumulation In Tissuessupporting
confidence: 76%
See 1 more Smart Citation
“…Keller et al (2004a) reported lipid content from 0.255 % to 64.7 % in loggerhead turtles captured in Core Sound, North Carolina. It is possible that some turtles did not eat and therefore lost fat reserves when kept in captivity 5-10 days (food was provided ad libitum) during egg induction and PHA skin tests (Yu et al 2011). Among the 26 PCB congeners evaluated in all samples, seven congeners were above detection limit including 3 mono-ortho congeners (PCB 28, 118, and 123) and 4 di-ortho congeners (PCB 101, 153, 170, and 180).…”
Section: Resultsmentioning
confidence: 99%
“…Phytohemagglutinin (PHA) skin test was also conducted to determine stimulation index (PHA SI), which is an indication of T-cell mediated immunity. Trapping, blood collection, and determination of hematological and immunological parameters have been described in detail in Yu et al (2011). Hematology and PHA SI were only determined in turtles collected in 2008.…”
Section: Methodsmentioning
confidence: 99%